EXPLORING THE IMPACT OF WORK-LIFE BALANCE ON EMPLOYEE PRODUCTIVITY IN HYBRID WORK SETTINGS - Ibnu Munzir; Suriyanti Suriyanti; Mahfudnurnajamuddin Mahfudnurnajamuddin (ITB AAS Indonesia Surakarta, 2025)
Work-life balance (WLB) has become a critical factor in shaping employee outcomes within hybrid work environments that combine remote and on-site arrangements. This study aims to examine the impact of work-life balance on employee productivity in hybrid work settings, emphasizing the mediating role of job satisfaction and the moderating effect of organizational support. Using a quantitative approach, survey data were collected from 250 employees across multiple industries implementing hybrid work systems in Indonesia. The results reveal that a higher level of work-life balance significantly enhances employee productivity through increased job satisfaction. Moreover, organizational support strengthens the positive relationship between WLB and productivity, suggesting that human resource strategies should prioritize flexible work policies, supportive leadership, and digital collaboration tools. The findings provide theoretical implications for sustainable HRM practices and practical insights for organizations seeking to optimize performance in post-pandemic employment landscapes..